JOB SATISFACTION AS A MEDIATOR OF THE RELATIONSHIP BETWEEN WORK FACTORS AND ORGANIZATIONAL COMMITMENT AMONG WOMEN IN MINING - Jeffry Jeffry; Qornul Manazil; Safril Rizki Waluyo; Tengku Mohd Khairal Abdullah (SOSIOEDUKASI, 2025)
Women working in male-dominated industries such as mining often face distinctive organizational challenges related to work-life integration, job-role alignment, and inclusion. Drawing on theories of person-job fit and organizational commitment. This research delves into the connections between balancing work and personal life, matching individuals to suitable job roles, promoting diversity and inclusion, and how they all impact the job satisfaction and dedication to the organization amongst women working in the coal mining industry in Indonesia. Information was gathered from 169 female workers via a detailed online questionnaire and studied using PLS-SEM. Findings indicate that the compatibility of a person with their job has the most significant positive impact on job satisfaction, while work-life balance shows a negative correlation. Diversity and inclusion also exhibit a significant, though comparatively weaker, positive relationship with job satisfaction. Furthermore, job satisfaction fully mediates the effects of the independent variables on organizational commitment. These findings extend prior research on gendered work environments by highlighting the central role of job satisfaction as a mechanism linking contextual work factors to attitudinal outcomes in underrepresented female employee populations.